Peran Orang Tua sebagai Katekis Utama dalam Keluarga: Membangun Generasi Muda yang Beriman - Ambrosius Sipriadi; Arnaldo Cardoso (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2024)
The focus of the writing of this article is on “How the role of parents as the main catechist of the family in building a faithful young generation. The purpose of writing this article is to explore and discover how the important role of parents in religious education for children, as well as the responsibility of parents in instilling religious and moral values in children. Support from the family can strengthen the relationship between parents and children so that parents can easily play a role in teaching and fostering children's faith. In writing this article, the author used a qualitative method with a literature approach. The author found that the family is the first and main place in the growth of a child, so the role of the family is very important in fostering and educating the faith of a child. Children who are raised in a religious family are more likely to become mature people in improving their faith patterns. Family catechesis is one of the most important and evolving topics. But on the one hand, family catechesis also faces challenges. These challenges are sometimes related to lack of time, difficulty in communicating about the faith of children, the influence of outside culture, the influence of technological development, and association in the modern world. With these challenges, what is the role of parents in the family to educate and foster the faith of children to become mature religious.